Factors Influencing Farmers' Decisions in Selling Chili to the Auction Market of Sleman Regency - Widayanto, Budi; Ngadirin, Eko Sugianto; Senjawati, Nanik Dara (Jurnal Dinamika Sosial Ekonomi, 2025)
This study aims to identify the mechanism of the chili auction market in Sleman Regency and analyse the influence of formation access, market location, income, social capital and auction market objectives on farmers' decisions in selling chili to the Sleman Regency auction market. The research uses a quantitative approach with a survey method. Location determination by purposive method. Samples were taken using the disproportionate stratified random sampling. The types of data used primary data and secondary data. Data collection methods through observation, interviews, and documentation. The analysis used descriptive analysis and logistic regression analysis. The results showed that: (1) the auction market mechanism starts from the transportation of chili by farmers from the land to the collection point, weighing, sorting and grading, digital auction, packaging to picking up and selling chili by traders, (2) the variables of access to information, social capital, and auction market objectives partially affect farmers' decisions. In contrast to the variables of market location and profits which partially have no effect on farmers' decisions to sell chili. All independent variables simultaneously affect the decision of farmers to sell chili peppers to the Sleman Regency auction market.